A comparison of re‐presentation and modified chin prompt to treat different topographies of liquid expulsion. Issue 4 (30th July 2021) - Ibañez, Vivian F.; Peters, Kerri P.; Vollmer, Timothy R.
Abstract : Treatment of one behavior in the chain of consumption might be associated with the emergence of other problematic behaviors. For example, some children with feeding disorders expel liquid. Moreover, the form in which children expel liquid might vary and influence whether a treatment to reduce liquid expulsion will result in clinically meaningful outcomes. In the current investigation, we first identified topographies of liquid expulsion (e.g., forceful, run out) for each child. We then compared and evaluated the effects of 2 procedures, a modified chin prompt and re‐presentation, on the liquid expulsion of 3 children with feeding disorders. For 2 participants, expulsion decreased to clinically meaningful levels with a modified chin prompt or re‐presentation. However, for 1 participant, expulsion decreased to clinically meaningful levels only when we combined the modified chin prompt and re‐presentation as part of a treatment package. We discuss possible mechanisms underlying the effects of a modified chin prompt and re‐presentation, in addition to areas for future research.